PENATALAKSANAAN CEDERA TENDINITIS PATELLA PADA ATLET BULUTANGKIS - Zeth Boroh, Nani Cahyani (Jorpres (Jurnal Olahraga Prestasi), 2016)
ABSTRACT Badminton is a popular sport in Indonesia becoming a mainstay in the international events as proven by the number of Olympic gold medals achieved. Badminton includes high intensity sport, multi-direction, and run-jump movements with acceleration-deceleration. Thus, badminton athletes are prone to the risk of knee injury, such as patellar tendinitis. In general, patellar tendonitis occurs in sports that contain many numbers of repeated jumping and running that result in inflammation in the patellar tendon. These injuries are also associated with excessive load during weight lifting, condition of the hip anatomy, blow to the knees and flat feet. This article discusses knee anatomy, patellar tendinitis definition, epidemiology, biomechanics of injury, sign and symptoms, physical examination, causes, diagnosis, differential diagnosis, management and rehabilitation. Keywords: Tendinitis patella, badminton, sports injury ABSTRAK Bulutangkis merupakan olahraga andalan Indonesia di kancah internasional. Olahraga ini juga popular di Indonesia dan menjadi olahraga tradisi emas di Olimpiade. Bulutangkis termasuk olahraga dengan intensitas tinggi, multi direksi, melompat, berlari dan akselerasi-deselerasi sehingga memiliki risiko terjadi cedera lutut, salah satunya tendinitis patella. Tendinitis patella umumnya terjadi pada olahraga yang banyak melakukan melompat dan berlari secara berulang-ulang yang menyebabkan munculnya radang pada tendon patella. Cedera ini juga terjadi akibat beban berlebihan saat mengangkat beban, kondisi anatomi pinggul, adanya pukulan pada lutut dan telapak kaki yang rata. Artikel ini membahas tentang anatomi lutut, definisi tendinitis patella, epidemiologi, biomekanika cedera, gejala, pemeriksaan fisik, penyebab, diagnosis, diagnosis banding, penatalaksanaan dan rehabilitasinya. Kata Kunci: Tendinitis Patella, bulutangkis, cedera olahraga